Knowledge, Attitude, and Practices of Araling Panlipunan Teachers Towards Reflective Approach: An Input for Learning Action Cell - Ephraim D, Clemen John; Hernando Jr. L., Bernal (Randwick International of Education and Linguistics Science Journal, 2025)
As online, blended, and face-to-face instruction modalities are getting more popular, reflective approaches to instruction could improve learning outcomes in the Philippines. This shift demands that educational approaches be critically reevaluated. Enhancing the quality of instruction in the Araling Panlipunan subject requires an understanding of teachers' reflective approach-related knowledge, attitudes, and practices (KAP). Offering insights into current use in the Philippine educational setting, this study examines the KAP of Araling Panlipunan teachers toward reflective teaching. Using a sequential mixed-methods research design, the study first collected quantitative data via questionnaires, then collected qualitative data from 50 teacher respondents through semi-structured interviews. The results show a "Very High" degree of knowledge and a positive attitude toward reflective approaches, especially in debates and essays. The curriculum's focus on material, however, limits opportunities for critical thinking, making it difficult for students to use these methods effectively. The suggested Learning Action Cell (LAC) programs seek to improve teacher skills through collaborative problem-solving, sharing of knowledge, and training to address these challenges. According to the study, professional development and resource allocation can greatly enhance teaching quality by incorporating workshops focused on reflective teaching and encouraging peer support, which would ultimately promote student learning and teacher development.